Cow’s milk allergy in patients with diarrhea - Nanis S Marzuki; Arwin AP Akib; I Boediman (Paediatrica Indonesiana, 2004)
Background Cow’s milk allergy (CMA) might be one of the causesof diarrhea in children. Previous prospective studies found theprevalence of CMA in children aged 0-3 years between 1.1-5.2%,but data about the prevalence of CMA in children with diarrheawas very limited.Objective This study intended to estimate the prevalence of CMAin children with diarrhea.Methods Children aged 0-3 years, who came with diarrhea andconsumed milk formula were selected for further evaluation. Adiagnostic procedure was developed i.e., elimination diet with par-tially hydrolyzed formula (pHF) for 2 weeks, and then open milkchallenge. If diarrhea was not resolved with pHF, the children weregiven extensively hydrolyzed formula, or soy-based formula.Results Ninety-nine children participated in this study, 87 camewith acute diarrhea and 12 with chronic diarrhea. There were 3children (2 children with acute diarrhea and one with chronicdiarrhea) who reacted to the milk challenge.Conclusion The estimated prevalence of CMA in children withdiarrhea in our study was 3%